The role of TCF3 as potential master regulator in blastemal Wilms tumors. Issue 6 (13th November 2018) - Kehl, Tim; Schneider, Lara; Kattler, Kathrin; Stöckel, Daniel; Wegert, Jenny; Gerstner, Nico; Ludwig, Nicole; Distler, Ute; Tenzer, Stefan; Gessler, Manfred; Walter, Jörn; Keller, Andreas; et al.
Abstract : Wilms tumors are the most common type of pediatric kidney tumors. While the overall prognosis for patients is favorable, especially tumors that exhibit a blastemal subtype after preoperative chemotherapy have a poor prognosis. For an improved risk assessment and therapy stratification, it is essential to identify the driving factors that are distinctive for this aggressive subtype. In our study, we compared gene expression profiles of 33 tumor biopsies (17 blastemal and 16 other tumors) after neoadjuvant chemotherapy. The analysis of this dataset using the Regulator Gene Association Enrichment algorithm successfully identified several biomarkers and associated molecular mechanisms that distinguish between blastemal and nonblastemal Wilms tumors. Specifically, regulators involved in embryonic development and epigenetic processes like chromatin remodeling and histone modification play an essential role in blastemal tumors. In this context, we especially identified TCF3 as the central regulatory element. Furthermore, the comparison of ChIP‐Seq data of Wilms tumor cell cultures from a blastemal mouse xenograft and a stromal tumor provided further evidence that the chromatin states of blastemal cells share characteristics with embryonic stem cells that are not present in the stromal tumor cell line. These stem‐cell like characteristics could potentially add to the increased malignancy and chemoresistance of the blastemal subtype. Along with TCF3, we detected several additional biomarkers that are distinctive for blastemal Wilms tumors after neoadjuvant chemotherapy and that may provide leads for new therapeutic regimens. Abstract : What's new? Wilms tumors (WT) that exhibit a blastemal subtype after neoadjuvant chemotherapy have an increased malignancy. Although individual (epi)genetic regulators and stem cell factors are important in the pathogenesis of blastemal WT, a systematic evaluation of the influence of a large array of transcriptional regulators has not yet been conducted. Our study identifies TCF3 as the driving regulatory element controlling central epigenetic processes deregulated in blastemal WT, together with many other regulators involved in chromatin remodeling, embryonic development, or pluripotency of embryonic stem cells. These insights may be used in the future to improve diagnosis, prognosis, or therapy of WT patients.